2022
DOI: 10.1136/bmjopen-2022-061002
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a real-world evaluation of an integrated child and family health hub for migrant and refugee women

Abstract: IntroductionContinuity of child and family healthcare is vital for optimal child health and development for developmentally vulnerable children. Migrant and refugee communities are often at-risk of poor health outcomes, facing barriers to health service attendance including cultural, language, limited health literacy, discrimination and unmet psychosocial needs. ‘Integrated health-social care hubs’ are physical hubs where health and social services are co-located, with shared referral pathways and care navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Data collection for the qualitative interviews and focus groups will continue until data saturation- no new themes pertaining to the research objectives are identified with subsequent interviews. However, from previous experience, we will contact at least 40 practitioners, managers and families/carers across the three sites, ensuring diversity with regard to practice and role [ 36 ].…”
Section: Study Methodsmentioning
confidence: 99%
“…Data collection for the qualitative interviews and focus groups will continue until data saturation- no new themes pertaining to the research objectives are identified with subsequent interviews. However, from previous experience, we will contact at least 40 practitioners, managers and families/carers across the three sites, ensuring diversity with regard to practice and role [ 36 ].…”
Section: Study Methodsmentioning
confidence: 99%
“…fostering relationships between service providers and service users to improve the cultural responsiveness of services [39,59,60,71]. Their support and education can increase health literacy, reinforce the importance of maternal and CFH health, and child developmental assessments, in order to optimise health outcomes [20,72]. Importantly, memories associated with pregnancy, birth, and early parenting are often powerful and long lasting [73], these experiences can in uence how women and families perceive and engage with health services in the future [20,74].…”
Section: Overview Of Ndings In Relation To Prior Studiesmentioning
confidence: 99%